ALTERATION IN HAEMATOLOGICAL PARAMETERS OF LABEO ROHITA (HAMILTON) EXPOSED TO DIFFERENT CONCENTRATIONS OF SEWAGE WATER - ROUT, SANGRAM KESHARI; BEHERA, LOPAMUDRA; SONA, B R; JANA, DEBASMITA; CHAKRABORTY, SRIPARNA; ANUPAMA, R R (Journal of the Inland Fisheries Society of India, 2021)
The study examined the effect of sewage water on certain haematological parameters of Labeo rohita exposed to four sub-lethal concentrations (25%, 50%, 75%, and 100%) of sewage for a period of 90 days. Among the haematological parameters, red blood cell (RBC) count, white blood cell (WBC) count and the haemoglobin (Hb) concentration levels decreased with the increase in sewage concentration. The study revealed that 100% concentration of sewage or raw sewage has serious impacts on fish. The changes in haematological parameters of the test fish indicated that the fish was under stress from poor physico-chemical parameters of sewage water, namely, NH3-N, BOD, COD and TDS. It is suggested that haematological parameters could be used as biomarkers for evaluation of environmental stress. Key words: Sewage, Haematological parameters, physico-chemical parameters, Labeo rohita